2022
DOI: 10.46328/ijres.2758
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Students’ Learning English through Social Media: A Case Study in Nepal

Abstract: This article reports an analysis of secondary students' experiences of using social media for learning English. It employed qualitative interpretative research design and taken online semi-structured interviews with the participants and their classes were observed to obtain qualitative information. The findings reveal that how social media helps secondary students for learning English formally inside the classroom and informally out of the classroom providing extra resources of English to improve listening, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…There are also exclusion criteria, such as articles that are unrelated to the current title and have a discussion subject that is unrelated to the intended topic are eliminated, example Social Media & English Learners' Academic Literacy Development (Shin, 2018), were excluded a research (Ghimire, 2022), and (Aleisa, 2022). These articles are unrelated to the research subject since they are unable to assist in searches relating to the use of social media in increasing EFL learners' writing skills.…”
Section: Methodsmentioning
confidence: 99%
“…There are also exclusion criteria, such as articles that are unrelated to the current title and have a discussion subject that is unrelated to the intended topic are eliminated, example Social Media & English Learners' Academic Literacy Development (Shin, 2018), were excluded a research (Ghimire, 2022), and (Aleisa, 2022). These articles are unrelated to the research subject since they are unable to assist in searches relating to the use of social media in increasing EFL learners' writing skills.…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation related to sharing pertains to the issue of screen sharing since Facebook does not have such a feature. Ghimire (2022), on the other hand, reported in his study about an English teacher who used Facebook as one of the social media in her class. He found that its use was an issue among the students in the teacher's class.…”
Section: Limitations Of Using Facebook In Teachingmentioning
confidence: 99%
“…This can lead to a lack of confidence in using social media platforms, as well as a lack of understanding of how to maximize the potential of these tools to enhance learning and promote higher-order thinking skills (HOTS) among students. Additionally, according to Ghimire (2022), there may be concerns about the appropriateness of social media use in the classroom and about privacy, safety, and cyberbullying. Therefore, there is a need for professional development and support to help teachers effectively integrate social media into their language teaching practice while promoting a safe and positive learning environment.…”
Section: Concern About Social Media Used In Language Teachingmentioning
confidence: 99%